Incidence of cough from acute exposure to fine particulate matter (PM2.5) in Madagascar: A pilot study - Zimmer, Alexandra J.; Tsang, Lai Yu; Jolicoeur, Gisèle; Tannir, Bouchra; Batisse, Emmanuelle; Pando, Christine; Sadananda, Gouri; McKinney, Jesse; Ambinintsoa, Ideal Vincent; Rabetombosoa, Roger Mario; Knoblauch, Astrid M.; Rakotosamimanana, Niaina; et al. (PLOS global public health, 2024)
Prolonged exposure to fine particulate matter (PM 2.5 ) is a known risk to respiratory health, causing chronic lung impairment. Yet, the immediate, acute effects of PM 2.5 exposure on respiratory symptoms, such as cough, are less understood. This pilot study aims to investigate this relationship using objective PM 2.5 and cough monitors. Fifteen participants from rural Madagascar were followed for three days, equipped with an RTI Enhanced Children’s MicroPEM PM 2.5 sensor and a smartphone with the ResApp Cough Counting Software application. Univariable Generalized Estimating Equation (GEE) models were applied to measure the association between hourly PM 2.5 exposure and cough counts. Peaks in both PM 2.5 concentration and cough frequency were observed during the day. A 10-fold increase in hourly PM 2.5 concentration corresponded to a 39% increase in same-hour cough frequency (incidence rate ratio (IRR) = 1.40; 95% CI: 1.12, 1.74). The strength of this association decreased with a one-hour lag between PM 2.5 exposure and cough frequency (IRR = 1.21; 95% CI: 1.01, 1.44) and was not significant with a two-hour lag (IRR = 0.93; 95% CI: 0.71, 1.23). This study demonstrates the feasibility of objective PM 2.5 and cough monitoring in remote settings. An association between hourly PM 2.5 exposure and cough frequency was detected, suggesting that PM 2.5 exposure may have immediate effects on respiratory health. Further investigation is necessary in larger studies to substantiate these findings and understand the broader implications.